Effort but not reward sensitivity is altered by acute sickness induced by experimental endotoxemia in humans - Draper, A; Koch, R; van der Meer, J; Apps, M; Pickkers, P; Husain, M; van der Schaaf, M (Springer Nature, 2017)
Sickness behavior in humans is characterized by low mood and fatigue, which have been suggested to reflect changes in motivation involving reorganization of priorities. However, it is unclear which specific processes underlying motivation are altered. We tested whether bacterial endotoxin E. coli lipopolysaccharide (LPS) affected two dissociable constructs of motivational behavior, ie, effort and reward sensitivity. After familiarization with 5 effort levels, participants made a series of accept/reject decisions on whether the stake offered (1, 4, 8, 12, or 15 apples) was 'worth the effort' (10%, 27.5%, 45%, 62.5%, and 80% of maximal voluntary contraction in a hand-held dynamometer). Effort and reward levels were parametrically modulated to dissociate their influence on choice. Overall, 29 healthy young males were administered LPS (2 ng/kg; n=14) or placebo (0.9% saline; n=15). The effort-stake task, and self-reported depression and fatigue were assessed prior to LPS/placebo injection, 2 and 5 h post injection. Cytokines and sickness symptoms were assessed hourly till 8 h after LPS injection. LPS transiently increased interleukin-6 and tumor necrosis factor-α, sickness symptoms, body temperature and self-reported fatigue, and depression post injection relative to baseline and placebo. These changes were accompanied by LPS-induced decreases in acceptance rates of high-effort options, without significantly affecting reward sensitivity 2 h post injection, which were partially recovered 5 h post injection. We suggest that LPS-induced changes in motivation may be due to alterations to mesolimbic dopamine. Our behavioral paradigm could be used to further investigate effects of inflammation on motivational behavior in psychiatric and chronic illnesses.Neuropsychopharmacology advance online publication, 15 November 2017; doi:10.1038/npp.2017.231.